Transforming Muslim Family Education: The Potential of AI and Digital Platforms for Empowerment - Amanina, Nilna; Salim, Hakimuddin (Universitas Muhammadiyah Surakarta, 2025)
The Muslim family is the smallest unit in society that has an important role in shaping the character of children through the application of Islamic values for happiness in this world and in the hereafter. Family Development begins with the formation of the personality of each family member, especially in childhood, which is a golden period in the formation of character. In the digital age, the emergence of artificial intelligence and various online platforms have changed the pattern of Islamic education in families, while presenting new opportunities and challenges for Muslim parents. The purpose of this study is to analyze the potential and challenges of utilizing AI and digital platforms in empowering Muslim families in educating children in accordance and how parents can face challenges in the digital era to shape the character of children in accordance with Islamic values. This research uses qualitative methods of literature studies, by collecting and analyzing data from books, scientific journals, and digital sources relevant to AI-based learning and Islamic Family Education. The results show that AI and digital platforms have the potential to improve the formation of children's Islamic character through interactive and visual learning experiences that support moral and spiritual development. However, the study also highlights the existence of ethical risks such as exposure to inappropriate content, as well as excessive dependence on technology that can weaken the immediate moral role of parents. Compared to traditional Islamic educational methods such as example, advice, and habituation. Digital Learning offers flexibility and accessibility, but it lacks in emotional depth and spiritual experience.